2018
DOI: 10.1088/1361-6501/aa99fc
|View full text |Cite
|
Sign up to set email alerts
|

The MeteoMet2 project—highlights and results

Abstract: Launched in 2011 within the European Metrology Research Programme (EMRP) of EURAMET, the joint research project "MeteoMet" -Metrology for Meteorology -is the largest EMRP consortium: National Metrology Institutes, Universities, meteorological and climate agencies, Research Institutes, collaborators and manufacturers are working together, developing new metrological techniques, as well as improving already existing ones, for meteorological observations and climate records. The project focuses on: humidity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Italian National Institute of Metrology (INRiM) staff were requested to join the evaluation committee. Recent work at INRiM included research activities and scientific production of direct interest for the present study: development of specific calibration systems and procedures (Musacchio et al, ), also for application in extreme environmental conditions (Musacchio et al, ), inclusion of changes in temperature standards for temperature series and extremes (Pavlasek et al, ), and specifically with the coordination of the large European project “MeteoMet—Metrology for Meteorology (Merlone et al, ; ). Both the Mitribah and Turbat stations were asked to send the thermometers that recorded the extreme temperature values to INRiM, where staff were made available for this study that requested specific calibration and comparison procedures.…”
Section: Metadata For Mitribah Kuwait and Turbat Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Italian National Institute of Metrology (INRiM) staff were requested to join the evaluation committee. Recent work at INRiM included research activities and scientific production of direct interest for the present study: development of specific calibration systems and procedures (Musacchio et al, ), also for application in extreme environmental conditions (Musacchio et al, ), inclusion of changes in temperature standards for temperature series and extremes (Pavlasek et al, ), and specifically with the coordination of the large European project “MeteoMet—Metrology for Meteorology (Merlone et al, ; ). Both the Mitribah and Turbat stations were asked to send the thermometers that recorded the extreme temperature values to INRiM, where staff were made available for this study that requested specific calibration and comparison procedures.…”
Section: Metadata For Mitribah Kuwait and Turbat Pakistanmentioning
confidence: 99%
“…In the framework of European project MeteoMet (Merlone et al, ; ) the self‐heating of HMP 155 sensors was evaluated both in a climatic chamber and in a wind tunnel (Izquierdo et al, ). Results of that study showed a significant contribution to temperature readings due to self‐heating.…”
Section: Metrology Analysis (Mitribah Kuwait Sensor)mentioning
confidence: 99%
“…This work was supported by the project ENV58 MeteoMet2 “Metrology for essential climate variables” included in the frame programme EMRP (Merlone et al, ; ). The EMRP is jointly funded by the EMRP participating countries within EURAMET and the European Union.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The metrological method proposed is addressed at understanding, evaluating and including the phenomenon in t air measurements and associated uncertainty. This work was developed within the numerous metrological activities of the European project MeteoMet-Metrology for Meteorology (Merlone et al, 2015a(Merlone et al, , 2018. The purpose of the work is to propose an experimental method for evaluation of the difference between readings of sensors exposed to reflected radiation from snow-covered surfaces with respect to natural soil, in the same site/area, and its inclusion in the overall t air measurement uncertainty budget.…”
Section: The Observed Phenomenonmentioning
confidence: 99%